Water quality. Determination of perfluoroalkyl and polyfluoroalkyl substances (PFAS) in water. Method using solid phase extraction and liquid chromatography-tandem mass spectrometry (LC-MS/MS). (4th November 2019) - British Standards Institution,
No abstract available